PENGEMBANGAN ALAT PERAGA PLACE VALUE BERBASIS SPEDOMATIK UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS II SD - Nopiyah; Awalina Barokah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a place value learning tool based on "Spedomatik" toimprove the understanding of mathematical concepts in grade II elementary schoolstudents. The research uses the ADDIE development model which includesAnalysis, Design, Development, Implementation, and Evaluation stages. Datacollection techniques included interviews, observations, questionnaires, and tests.The subjects were 28 second-grade students at SD Islam Insan Taqwa. Theresults showed that the developed Spedomatik media met valid, practical, andeffective criteria. This was based on expert validation results with an averagepercentage of 81.6% (very valid), teacher and student responses with an averageof 85% (very practical), and student learning outcomes that increased significantlyafter the use of the media. Thus, Spedomatik-based place value media is suitableto be used as a learning aid to enhance students’ conceptual understanding inmathematics.